Autonomy in the relationship between education and entrepreneurial intentions of female students - Tuyen Thi Kim Dinh; Trang Duong Thuy Mai; Linh Thi Thuy Ly; Minh Pham (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
Female students are a potential target that can help the economy develop and grow. Although women starting businesses has become popular, women still face many more challenges than men in the Vietnamese market. Some of them are autonomy, knowledge, and business motivation. Therefore, this study aims to evaluate the impact of entrepreneurship education on female students’ entrepreneurial intention through business motivation. At the same time, the research also examines the moderating role of autonomy in relationships. Data were collected from 356 female students at universities in Vietnam and analyzed using SmartPLS 4 software. The results of the study accepted all hypotheses in the model. The study found that business motivation mediates the relationship between entrepreneurship education and entrepreneurial intention. Autonomy has a moderating role in the relationships in the model. Therefore, universities need to improve entrepreneurship education and autonomy so that female students have more motivation to start businesses, thereby increasing the rate of female entrepreneurs in Vietnam.